Current approaches in the treatment of bladder cancer and policy in Marmara University Hospital - (:unkn) unknown (Kluwer Academic Publishers, 1990)
Bladder cancer is one of the malignancies encountered frequently in urological practice. Since the three main treatment modalities (surgery, chemotherapy and radiotherapy) may be used alone or together, there are many treatment options. In this paper the current approaches in the treatment of bladder tumours are reviewed and the policy in Marmara University Hospital is described. © 1990 Akadémiai Kiadó.